Doping GaN NPs Synthesized by a Chemical Method for p-n Junction Application - Qaeed, Motahher. A.; Mindil, A.; Eid, Alharthi A. (International Journal of Membrane Science and Technology, 2023)
This research was devoted to studying the doping of GaN NPs at low temperature with Mg and the possibility of using them in the p-n junction. This study was subjected to a FESEM, EDX, XRD, PL and Hall Effect examination. The FESEM examination showed clear images of the NPs, the XRD peaks appear at 2? = 32.5, 39.1 and 45.48 which conform the crystalline of p-GaN NPs, Hole Effects measurements confirm the p-GaN with different Mg ratios. The ideality factor and series resistance of p-n junction have been measured.